Tasawuf dan Penyembuhan: Studi atas Air Manaqib dan Tradisi Pengobatan Jamaah Aolia, Panggang, Gunung Kidul, Yogyakarta - Ida Novianti; Arif Hidayat (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2020)
This paper attempts to examine the values and meanings behind the tradition that developed in the Jamaah Aolia Panggang, Yogyakarta had strong beliefs related to Banyu Manaqib as a cure for disease. As a result, First, values and meanings behind the tradition that developed in the Jamaah Aolia Panggang, Yogyakarta had strong beliefs related to Banyu Manaqib as a cure for disease. The worshipers spread out in these various regions only have a division of priests in their respective regions. The belief held by the Jamaah Aolia Panggang is that their need of reading shalawat, pray for aulia through hymns, and prayers for martyrs and believers since living. Second, Banyu Manaqib as a cure for disease in the praying water in which the prayer is contained. The particles have been aligned and focused so that it is easier to integrate in repairing damaged body cells. The performance of water in cleansing the body will be optimized after having prayers. Dialectics of microcosm and macrocosm based on the method of